A REVIEW ON EPIGENETIC REGULATION IN BACTERIAL PATHOGENESIS AND RESISTANCE - Abdzaid, Ahmed Majeed; Jabbar, Ali Sabri (Journal of Medical Genetics and Clinical Biology, 2024)
The study of bacterial Bacterial epigenetics has become important ,because it help to understanding the mechanisms used by bacteria to regulate gene expression with keeping their DNA sequence. This regulation has been known to play an important role in bacterial pathogenesis and resistance mechanisms, which assit the bacteria to easily adapt to the environmental changes and withstand hard conditions, including antibiotic exposures. In this review we clarify the essential mechanism of epigenetic regulation of the bacteria that include, DNA methylation, histone-like protein modifications, and non-coding RNAs. We focus into their importance to bacterial virulence and resistance, focusing on understanding how to use ne therapeutic strategies against antibiotic resistance and invasive diseases